Video Streaming over Vehicular Ad Hoc Networks: A Comparative Study and Future Perspectives - Ghafoor, Kayhan Z. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
Vehicular Ad Hoc Network (VANET) is emerged as an important research area that provides ubiquitous short-range connectivity among moving vehicles. This network enables efficient traffic safety and infotainment applications. One of the promising applications is video transmission in vehicle-to-vehicle or vehicle-to-infrastructure environments. But, video streaming over vehicular environment is a daunting task due to high movement of vehicles. This paper presents a survey on state-of-arts of video streaming over VANET. Furthermore, taxonomy of vehicular video transmission is highlighted in this paper with special focus on significant applications and their requirements with challenges, video content sharing, multi-source video streaming and video broadcast services. The comparative study of the paper compares the video streaming schemes based on type of error resilient technique, objective of study, summary of their study, the utilized simulator and the type of video sharing. Lastly, we discussed the open issues and research directions related to video communication over VANET.